Towards an integral pedagogy in the age of 'digital Gestell': Moving between embodied co-presence and telepresence in learning and teaching practices. Issue 5 (November 2022) - Aroles, Jeremy; Küpers, Wendelin
Digitalisation offers a wide array of opportunities, but also challenges, for universities and business schools alike, regarding the provision and delivery of their teaching and learning activities. The COVID-19 pandemic has highlighted some of these challenges, as it forced educational institutions to move their pedagogic activities online in line with new governmental regulations. In this article, we identify and discuss critically the following three interconnected challenges: (1) shifting from direct embodied co-presence to technologically mediated telepresence, (2) re-embodying teaching and learning activities and (3) rethinking the purpose and relevance of teachings in business schools. We explore these challenges through a phenomenological lens, informed by the Heideggerian concepts of enframing ( Gestell ) and releasement ( Gelassenheit ), with a focus on (re-)embodiment. Finally, we discuss the need, for teachers and learners, to be able to reflectively move between embodied and digital(ised) forms of learning and teaching and outline some implications and perspectives regarding the development of an integral pedagogy.